2014
DOI: 10.1002/mnfr.201300710
|View full text |Cite
|
Sign up to set email alerts
|

Excess α‐tocopherol decreases extrahepatic phylloquinone in phylloquinone‐fed rats but not menaquinone‐4 in menaquinone‐4‐fed rats

Abstract: Excess α-tocopherol decreased extrahepatic PK in rats fed PK but not MK-4 in rats fed MK-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
4
12
1
Order By: Relevance
“…This result could at least partially explain the excessive bleeding observed in patients supplemented with vitamin E (11). This result seems in disagreement with previous data obtained in rats and showing a non-significant decrease of phylloquinone serum concentration 6 h after gavage with 0.2 mg of phylloquinone and 10 mg of ␣-tocopherol (12). However, our data suggest that the phylloquinone absorption peak is probably earlier, around 3-4 h (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result could at least partially explain the excessive bleeding observed in patients supplemented with vitamin E (11). This result seems in disagreement with previous data obtained in rats and showing a non-significant decrease of phylloquinone serum concentration 6 h after gavage with 0.2 mg of phylloquinone and 10 mg of ␣-tocopherol (12). However, our data suggest that the phylloquinone absorption peak is probably earlier, around 3-4 h (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Although it has been confirmed that excess of ␣-tocopherol could affect phylloquinone metabolism, the mechanisms of this phenomenon have not been fully elucidated (12). We suggest that a competition with vitamin E could also take place with uptake transporters in the intestine and would thus lead to decreased vitamin K absorption.…”
mentioning
confidence: 79%
“…In their most recent study, Farley et al [235] concluded that α-TOH, or even α-CEHC, interferes with an intermediate step in the formation of tissue-specific menaquinone-4 from phylloquinone, such as alterations in the transport via chylomicrons or other lipoproteins or reductions of the cellular uptake of phylloquinone or menadione, an intermediate product of phylloquinone in the menaquinone formation pathway. This hypothesis is supported by findings of Hanzawa et al [236] who found that rats fed a diet with 0.75 mg/kg phylloquinone for six weeks have decreased phylloquinone tissue concentrations with supplementation of 100 mg α-TOH while in rats fed with 0.75 mg/kg menaquinone diet the tissue concentrations of menaquinone remained unchanged with an increased application of α-TOH.…”
Section: Interaction With Vitamin K Metabolismsupporting
confidence: 67%
“…Finally, the form of vitamin E also contributes to the interference with vitamin K metabolism, as γ-TOH is not as potent as α-TOH in decreasing extrahepatic phylloquinone concentrations [236] . Taken together, vitamin K metabolism is disturbed by vitamin E at the level of extrahepatic synthesis of menaquinone from phylloquinone or menadione and the different vitamin E forms also lead to differing effects on the metabolic interactions.…”
Section: Interaction With Vitamin K Metabolismmentioning
confidence: 99%
“…Among the vitamin K types, PK is added to the AIN93-rodent diet (16), which is widely used in animal experiments as a standard rodent diet. We have revealed that PK concentration in the extrahepatic tissues of rats fed the AIN93-rodent diet decreases as the vitamin E content in the diet increases (17). Consumption of a diet containing a 75 IU a-tocopherol/kg diet, a basal content of vitamin E in the AIN93-rodent diet, significantly lowered PK concentration in the various tissues except for the liver of rats, although consumption of a diet containing an excess amount of g-tocopherol lowered PK concentration in some tissues.…”
mentioning
confidence: 99%